Diversity of pollen morphology in species of Cercidoideae (Fabaceae) from Cerrado forest fragments, Brazil: Bauhinia L. and Schnella Raddi - Soares, Eduardo Lopes; Landi, Lorrayne Albernaz Domingues Camilo [UNESP]; de Souza, Cintia Neves [UNESP]; Lopes, Ana Carolina Venancio; Gasparino, Eduardo Custódio [UNESP] (Elsevier, 2024)
The Cercidoideae subfamily has a wide geographic distribution in Brazil, with its most representative genera, Bauhinia L. and Schnella Raddi. This study aims to describe the pollen morphology of native species of Bauhinia and Schnella that occur in forest fragments in southeastern Brazil, expanding the morphological knowledge of Cercidoideae species. The pollen morphology of 21 species of the subfamily Cercidoideae were analyzed, including 13 species of Bauhinia and eight species of Schnella. Pollen grains were acetolyzed, measured, and photographed in light microscopy, while pollen grains non-acetolyzed were used for analysis in scanning electron microscopy. Quantitative pollen grain data were examined by descriptive and multivariate analysis; qualitative data were described and used to define pollen types. The studied species showed pollen with variation in size, amb, polar area, shape, type, and detail of ectoaperture and endoaperture, exine ornamentation, and supratectal elements. Qualitative data allowed separating the Bauhinia and Schnella species into five pollen types according to the type of aperture and the exine ornamentation. The quantitative data of diameter, however, allowed the separation of genera and confirmed the pollen types in Bauhinia and Schnella. From the data obtained and the pollen variations observed in the species analyzed, we can describe the genera Bauhinia and Schnella as eurypalynous.
Keywords: Cerrado; Eurypalynous; Leguminosae; Palynology; Phanera; Vegetation biomes